Pendampingan Ibu Hamil Obesitas Dengan Asuhan Berkesinambungan (COC) - Gita, Estin; Nunik Adi Wahyuni; Wuri Widi Astuti (Universitas Nusantara PGRI Kediri, 2024)
Abstract Continuity of Care is one of the efforts to reduce AKI and AKB in pregnancy to family planning. The purpose of this mentoring activity is to provide care for Mrs.